Pregunta
upstudy study bank question image url

\( 2 x^{2}-3 x y=-4 \) and \( 4^{x+y}=2^{y+4} \)

Ask by Hodges Stephens. in South Africa
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solutions are \( x = 1, y = 2 \) and \( x = \frac{1}{2}, y = 3 \).

Solución

We are given the system of equations:   (1) 2x² – 3xy = –4   (2) 4^(x+y) = 2^(y+4) Step 1. Solve Equation (2): Write 4^(x+y) in terms of base 2. Since 4 = 2², we have   4^(x+y) = (2²)^(x+y) = 2^(2(x+y)). Thus, Equation (2) becomes   2^(2(x+y)) = 2^(y+4). Since the bases are the same and the exponential function is one-to-one, we can equate the exponents:   2(x+y) = y + 4. Now solve for y:   2x + 2y = y + 4   2x + 2y – y = 4   2x + y = 4   y = 4 – 2x. Step 2. Substitute y into Equation (1): Substitute y = 4 – 2x into 2x² – 3xy = –4:   2x² – 3x(4 – 2x) = –4. Expand and simplify:   2x² – 12x + 6x² = –4   (2x² + 6x²) – 12x = –4   8x² – 12x = –4. Bring –4 to the left side:   8x² – 12x + 4 = 0. Divide the entire equation by 2 to simplify:   4x² – 6x + 2 = 0. Step 3. Solve the Quadratic Equation: Use the quadratic formula for ax² + bx + c = 0. Here, a = 4, b = –6, and c = 2.   x = [–b ± √(b² – 4ac)] / (2a)   x = [6 ± √((–6)² – 4·4·2)] / (2·4)   x = [6 ± √(36 – 32)] / 8   x = [6 ± √4] / 8   x = [6 ± 2] / 8. Thus, the two solutions for x are:   x = (6 + 2)/8 = 8/8 = 1   x = (6 – 2)/8 = 4/8 = 1/2. Step 4. Find the Corresponding y Values: Recall y = 4 – 2x. For x = 1:   y = 4 – 2(1) = 4 – 2 = 2. For x = 1/2:   y = 4 – 2(1/2) = 4 – 1 = 3. Step 5. Verify the Solutions: For (x, y) = (1, 2):   Equation (1): 2(1)² – 3(1)(2) = 2 – 6 = –4 ✓   Equation (2): 4^(1+2) = 4³ = 64 and 2^(2+4) = 2⁶ = 64 ✓ For (x, y) = (1/2, 3):   Equation (1): 2(0.5)² – 3(0.5)(3) = 2(0.25) – 4.5 = 0.5 – 4.5 = –4 ✓   Equation (2): 4^(0.5+3) = 4^(3.5) = (2²)^(3.5) = 2^(7) = 128 and 2^(3+4) = 2^(7) = 128 ✓ The solutions satisfy both equations. Final Answer:   x = 1, y = 2  or  x = 1/2, y = 3.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

Let’s dive into some cool background! The equation \( 2x^2 - 3xy = -4 \) is a quadratic equation in terms of \( x \) and represents a curve in a 2D plane. It can open up insights into geometry, like conic sections. The second equation, \( 4^{x+y} = 2^{y+4} \), shows how exponential functions can be manipulated using properties of exponents. Remember, \( 4 \) can be expressed as \( 2^2 \), which can pave the way for simplifying this equation. Now, let’s consider how these equations might pop up in the real world! You could see similar quadratic equations when modeling projectile motion or calculating areas. The second equation often surfaces in finance when dealing with compound interest or population growth problems, where exponential relationships take the stage. Connecting mathematical models to real situations helps visualize the fantastic utility of these concepts!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad